Analysis and literature review of invasive and noninvasive blood pressure in a case of electrical injury leading to amputation (1例电击伤截肢患者的有创和无创血压分析并文献复习) - ZHU Yuling (朱玉玲); JIANG Qixia (蒋琪霞) (中西医结合护理)
Electric injury is one of the common injuries, accompanied by passage of high-voltage current through the body, usually with one entrance and multiple outlets. It easily leads to destructive injury, severe post-traumatic stress response and secondary infection, and the condition changes rapidly. Blood pressure monitoring is a common method to accurately and timely determine the condition. This article analyzed and compared the results of invasive and noninvasive blood pressure monitoring in a patient with bilateral upper limb and right lower limb amputation after high-voltage electrical injury, and summarized and discussed the differences between invasive and noninvasive blood pressure monitoring through literature review, providing references for clinical effective monitoring of blood pressure in patients with severe trauma. (电击伤是常见的创伤之一, 伴随高压电流通过身体, 通常有一个入口, 多个出口, 容易出现毁损性损伤、严重的创伤后应激反应及继发感染, 病情变化快。血压监测是准确、及时判断病情的常用方法。本文分析对比1例高压电击伤后双上肢、右下肢截肢患者的有创血压(IBP)无创血压(NBP)监测结果, 并通过文献复习, 总结讨论IBP、NBP监测之间差异性, 为临床有效监测重症创伤患者血压提供参考。)